Are human dental papilla-derived stem cell and human brain-derived neural stem cell transplantations suitable for treatment of Parkinson's disease? - Yoon, Hyung Ho; Min, Joongkee; Shin, Nani; Kim, Yong Hwan; Kim, Jin-Mo; Hwang, Yu-Shik; Suh, Jun-Kyo Francis; Hwang, Onyou; Jeon, Sang Ryong (SHENYANG EDITORIAL DEPT NEURAL REGENERATION RES, 2013)
Transplantation of neural stem cells has been reported as a possible approach for replacing impaired dopaminergic neurons. In this study, we tested the efficacy of early-stage human dental papilla-derived stem cells and human brain-derived neural stem cells in rat models of 6-hydroxydopamine-induced Parkinson's disease. Rats received a unilateral injection of 6-hydroxydopamine into right medial forebrain bundle, followed 3 weeks later by injections of PBS, early-stage human dental papilla-derived stem cells, or human brain-derived neural stem cells into the ipsilateral striatum. All of the rats in the human dental papilla-derived stem cell group died from tumor formation at around 2 weeks following cell transplantation. Postmortem examinations revealed homogeneous malignant tumors in the striatum of the human dental papilla-derived stem cell group. Stepping tests revealed that human brain-derived neural stem cell transplantation did not improve motor dysfunction. In apomorphine-induced rotation tests, neither the human brain-derived neural stem cell group nor the control groups (PBS injection) demonstrated significant changes. Glucose metabolism in the lesioned side of striatum was reduced by human brain-derived neural stem cell transplantation. [F-18]-FP-CIT PET scans in the striatum did not demonstrate a significant increase in the human brain-derived neural stem cell group. Tyrosine hydroxylase (dopaminergic neuronal marker) staining and G protein-activated inward rectifier potassium channel 2 (A9 dopaminergic neuronal marker) were positive in the lesioned side of striatum in the human. brain-derived neural stem cell group. The use of early-stage human dental papilla-derived stem cells confirmed its tendency to form tumors. Human brain-derived neural stem cells could be partially differentiated into dopaminergic neurons, but they did not secrete dopamine.